Penegakan Hukum Mengenai Hak Asasi Manusia (HAM) di Indonesia - Uyla Maylani; Damai Vistiani Gulo; Farhan Lutfhi Azidan (PLEDOI (Jurnal Hukum dan Keadilan), 2022)
Human rights are rights owned by humans as creatures created by God. Human rights have come a long way to fight for justice for people worldwide. Historically, the efforts taken to solve humanitarian problems have been carried out for a long time in the world, and no one knows for sure when human rights began to be fought for. The enforcement of human rights occurs because of the violation of the law. Enforcement of human rights is the duty of all levels of society, not only the duty of state institutions. All levels of society are expected to cooperate and help each other in upholding human rights to realize just and civilized human precepts and create a prosperous society. The formation of law cannot be separated from the decisions of judges (judge-made law) related to law enforcement, while law enforcement is essentially a process to realize the legal goals of legal ideas into reality. This paper examines aspects of human rights in the rule of law, between progressive law and positive law. Progressive law is pro-justice and pro-people law, meaning that in judging the legal actors are required to prioritize honesty, empathy, concern for the people, and sincerity in law enforcement. The authors chose this title because until now law enforcement, especially related to human rights in Indonesia is still not optimal, mainly because until now the State of Indonesia is still in a transition zone that is still characterized by legal uncertainty. The main problem in this article is how to apply the law to human rights violations, which institutions prosecute human rights violators, what are means of settlement used in cases of human rights violations in Indonesia, and what are the principles of Islamic law regarding human rights